Studies on the production of technetium-99m generators based on gel elution: Final Report - Castro, Manuel (1994)
Technetium-99m generator based on Ti Mo elution has been carried out. The gel matrix was prepared by mixing non-irradiated molybdate with Titanium Chloride solution. Conditions of preparing and drying Ti Mo were evaluated as a function of elution yield. Thus, pH and water content were found highly critical for reproductiveness of the results. Non-elutable form of Tc-99m can be oxidized treating the target after irradiation with K2Cr2O7 0.001M solution. During several experiments the columns were soaked with this oxidizing solution for one hour and afterwards the Ti Mo was washed with 150 ml physiological saline. Daily elutions were done with 10 ml of NaCl 0.9 %. Cooling water reactor during irradiation quartz ampoules has been studied. To study this effect, one group of samples were irradiated in aluminum caps air-tight screw and another one was irradiated in drilled caps with six holes to permit water reactor recirculation around quartz ampoules. By combination K2Cr2O7 target treatment and cooling Ti Mo during irradiation is possible to get yields of Tc-99m near to 76%. The radiochemical purity was > 99% and Al content < 10 ppm , Cr < 0.05 ppm , Mo <20 ppm, Ti was no detected. Biological scans practiced in animals have been considered satisfactory. (author).